2008
DOI: 10.1007/s00436-008-0897-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of folate derivatives on the activity of antifolate drugs used against malaria and cancer

Abstract: The folate derivatives folic acid (FA) and folinic acid (FNA) decrease the in vivo and in vitro activities of antifolate drugs in Plasmodium falciparum. However, the effects of 5-methyl-tetrahydrofolate (5-Me-THF) and tetrahydrofolate (THF), the two dominant circulating folate forms in humans, have not been explored yet. We have investigated the effects of FA, FNA, 5-Me-THF, and THF on the in vitro activity of the antimalarial antifolates pyrimethamine and chlorcycloguanil and the anticancer antifolates methot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 39 publications
3
32
0
2
Order By: Relevance
“…The evidence suggesting that oral 5‐methyl‐THF may act as a source of folates in humans without antagonising the activity of antifolate drugs against P. falciparum (Nduati et al , 2008) is promising but it is derived from a single in vitro study with only two P. falciparum laboratory strains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The evidence suggesting that oral 5‐methyl‐THF may act as a source of folates in humans without antagonising the activity of antifolate drugs against P. falciparum (Nduati et al , 2008) is promising but it is derived from a single in vitro study with only two P. falciparum laboratory strains.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, 5‐methyl‐ THF is a methyl donor in the methionine cycle (lower cycle, with metabolites in green), resulting in the production of tetrahydrofolate and methionine (blue dotted lines). Recent evidence from an in vitro study suggests, however, that this pathway is not effectively utilised in Plasmodium , either because 5‐methyl‐ THF monoglutamate from the erythrocytic pool cannot cross the membranes of the parasitophorous vacuole and the parasite (blue dotted line, with question mark) or because the parasite does not need methionine, because it derives this amino acid precursor of S‐adenosylmethionine from haemoglobin degradation or human plasma (Nduati et al , 2008). This evidence suggests that oral 5‐methyl‐ THF may act as a source of folates in humans without antagonising the in vitro activity of antifolate drugs against P. falciparum (Nduati et al , 2008; Nzila et al , 2014).…”
Section: Folate and Antifolate Metabolism In Plasmodium Parasitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Four controlled trials using different doses have shown that supplementation with 5-MTHF is at least as effective as folic acid in improving folate status in women of childbearing age (Houghton 2006;Lamers 2004;Venn 2002;Venn 2003). This form of folate may also be less likely to mask haematological symptoms of severe vitamin B 12 deficiency and it exhibits a lower interaction potential with antifolate antimalarial drugs (Nduati 2008;Pietrzik 2010), specifically sulphadoxine-pyrimethamine (SP), which might be affected by folic acid supplementation (Carter 2005;English 2006;Van Eijk 2008).…”
Section: Description Of the Interventionmentioning
confidence: 99%